BEMISIA TABACI B BIOTYPE INFESTATION AND SUGAR CONTENT ON LEAVES OF TOMATO CULTIVARS FERTIRRIGATED WITH POTASSIUM CHLORATE AND POTASSIUM SULPHATE - Feltrin, Deise Maria; Pott, Cristiano André; Furlani, Pedro Roberto; Carvalho, Cássia Regina Limonta (Revista de Ciências Agroveterinárias, 2004)
Bemisia tabaci B biotype (whitefly) has been responsible for many losses on tomatoes, mainly due to irregular ripening of the fruits and decrease on yield potential. The aim of this study was to evaluate the effect of different potassium sources (K-sources), fertirrigated by drip irrigation system, on the infestation of B. tabaci B biotype and on the sugar content on the leaves of three different tomato cultivars.The experiment was carried out on greenhouse at the Experimental Station of the Instituto Agronômico (IAC), São Paulo, Brazil, between September 2000 and January 2001. Potassium Chlorate (KCl) and Potassium Sulphate (K 2 SO 4 ) were used as K-sources. Sweet Million, Rocio and Densus were the selected cultivars. Plants were cultivated on slabs filled with agricultural substratum and fertirrigated with nutritive solution. Evaluated parameters were: number of eggs and nymphs on the plants at 20 and 40 days after whitefly infestation; and reducing sugars, sucrose and total sugars on the leaves. Results showed that K-sources did not have influence on the number of eggs and nymphs. On the second evaluation date, cultivar effect was significant on oviposition. Leaf sugar content were influenced by K-sources. Tomato plants fertirrigated with K 2 SO 4 on nutritive solution presented higher values, for total sugar content on the leaves, in comparison with the plants treated with KCl on nutritive solution.